O percurso de Freud no estudo da religião: contexto histórico e epistemológico, discursos e novas possibilidades - Maciel, Karla Daniele de Sá Araújo (2007)
Religion, with all its significant, is becoming a greater part in the contemporary context, having, therefore, its resonances in the practice of psychoanalytic clinic. In this context Freud was without a doubt, one of the authors that more theorized on this thematic, through its metapsychology. Thus this work has as objective to know Freud s passage in the study of the religious phenomenon. For this, a bibliographical methodology was used and this work was divided in three basic parts: the first one presents an exposition of the facts of Freud s life related to the religion, as well as, it makes a characterization of predominant scientific conception in his time. The second part brings two Freudian s speeches on the religious phenomenon. These speeches are characterized by a scientific position, in which they find the marks of the direct influence of the conceptions of science front to the religion, under Freud s position. The other position is the analytical one, thus called, for it says of the psychoanalytic contributions of Freud to the study of this thematic. The third and last part argues new reading and theoretical constructions possibilities existed in the proper text of the authors psychoanalysis contributions. Such possibilities are present in its theory, because of the permanent dialectic movement that characterizes Freud s way of research and writing. Therefore, complexity can be seen in his religious studies